2015
DOI: 10.1016/j.jvir.2015.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial Hepatic Chemoembolization with 70–150 µm Drug-Eluting Beads: Assessment of Clinical Safety and Liver Toxicity Profile

Abstract: Purpose To assess the incidence and severity of adverse events (AEs) in the form clinical symptoms and liver/biliary injuries (LBI) in patients with hepatic malignancies treated with transarterial chemoembolization using 70–150 μm drug-eluting beads (DEBs). Materials and Methods A single-institution retrospective analysis was performed in 37 patients (25 patients with hepatocellular carcinoma and 12 patients with metastatic disease) who underwent 43 sessions of segmental/subsegmental 70–150 μm DEB transarter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 27 publications
(34 reference statements)
5
28
2
Order By: Relevance
“…12,13 A study from Odisio et al, 14 where they used 70 -150 μm drug-eluting beads, pointed out an incidence of PES of 67.4%, which is also in the described range of 60% -80%. However, a study from Padia et al 15 that compared the safety of small (100 -300 μm) and mediumsize (300 -500 μm) particles, showed that the incidence of postembolization syndrome was lower in the first group and corresponded to 8%.…”
Section: Discussionmentioning
confidence: 97%
“…12,13 A study from Odisio et al, 14 where they used 70 -150 μm drug-eluting beads, pointed out an incidence of PES of 67.4%, which is also in the described range of 60% -80%. However, a study from Padia et al 15 that compared the safety of small (100 -300 μm) and mediumsize (300 -500 μm) particles, showed that the incidence of postembolization syndrome was lower in the first group and corresponded to 8%.…”
Section: Discussionmentioning
confidence: 97%
“…DEB-TACE was effective and tolerable in Chinese HCC patients with portal vein invasion, and previous C-TACE treatment appeared to be an important predictor of worse clinical outcome 18 . Moreover, the optimal particle size of DEBs for HCC patients receiving DEB-TACE treatment remains uncertain and not well studied 11,[19][20][21][22] . Lencioni et al 23 recommended that, in order to embolize the tumor thoroughly, a particle size range of 300-500 um is needed for tumors >5 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous efforts have been directed toward reducing the particle size of DEBs based on the hypothesis that microspheres of smaller size can penetrate more deeply into the arterioles of tumor tissues. Theoretically, small-size microspheres allow for more homogeneous intratumoral drug distribution and more distal vascular penetration 11 . This theory was supported by a recent study in patients with liver malignancies in whom DEBs with small diameters achieved improved the radiological response in terms of extensive intratumoral necrosis 12 .…”
mentioning
confidence: 99%
“…Currently available DEB size ranges between 70 and 300 lm which can be chosen depending on the target tumor vascularity. 16,21 Another limitation was the use of magnetic gradient coil inserts 14,18,20 which are more powerful than built-in imaging gradient coils but are not usable clinically due to their limited bore size. Prior studies also lack anatomical and physiological realism; they were either performed in nonbifurcating arteries, 17 in vitro in small animal models 14 or in nontubular channels with slow flow, which maximize steering efficiency due to the weakness of the magnetic force but that are not representative of physiologic rheological conditions.…”
Section: Magneticmentioning
confidence: 99%
“…One technical limitation of those studies was the use of large beads, which possess higher magnetization but are not optimal for hepatic embolization. Currently available DEB size ranges between 70 and 300 μm which can be chosen depending on the target tumor vascularity . Another limitation was the use of magnetic gradient coil inserts which are more powerful than built‐in imaging gradient coils but are not usable clinically due to their limited bore size.…”
Section: Introductionmentioning
confidence: 99%